A QUALIDADE DE VIDA NO TRABALHO DO MOTORISTA E AS RELAÇÕES DE TRABALHO SOB A PERSPECTIVA DA REGULAMENTAÇÃO DA PROFISSÃO: Um estudo de caso em uma empresa transportadora de combustíveis - BRUNETTI, MARIO LUIS (2016)
The purpose of this study was to investigate the quality of working life of drivers in a fuel transportation company from the advent of the regulation of the driver profession. This work approaches the subject-matter in the Research line of strategy when considering the balance between interests of the organization and individuals who work is an important tool ensuring the efficiency and productivity while serving the needs of workers. We sought to understand how work relationships and QWL take place between the drivers and the company after the regulation of the profession, and what is the perception of the main actors on the changes introduced in the profession as well as knowing the levels of satisfaction category with QWL. Thus, the aim of this study was to analyze the rules established in the regulations of the driver profession and the result of its implementation in the levels of satisfaction of QWL and in working relationships between professional drivers and road transport companies. This is a descriptive study, with qualitative and quantitative approach whose method was the only case study applied in a fuel transportation company. For the quantitative portion of the study, we used a questionnaire of Likert six-points escale, with semi-structured format developed from the evaluation model of QWL proposed by Walton (1973). The survey was made available to all drivers employed in the organization, totaling 202 possible participants, resulting in 152 considered valid. Of these, 20 were used in the pilot study conducted to evaluate the instrument developed. For the qualitative portion, we interviewed two drivers and two managers with the intention of investigating the vision of the company's managers and drivers about the changes in the organizational environment and how relationships work and QWL were affected by the regulation of the profession. It also serves as a support for triangulation with the quantitative portion. For treatment of qualitative data the technique of content analysis was applied . Quantitative data were analyzed statistically using the statistical package SPSS® (Statistical Package for Social Sciences). For verification and evaluation of data we used the central tendency, the scale reliability dispersion through the value of Cronbach's alpha and factor analysis measures. According to data produced by the study, in general, it is clear that the organization has positive characteristics that favor the QWL. The findings showed a satisfaction index higher than 70% in most valuation model factors of QWL proposed by Walton (1973). It was observed that the regulation of the profession mainly covered the following factors: a) fair and adequate remuneration; b) working conditions; and c) Work and total life space, for which the results show a level of satisfaction higher than 75%. It was clear that the regulation of the profession interfered positively in the organization of work routine of drivers and therefore in the QWL. The precariousness of work before perceived in previous studies was not observed in this study.